Effectiveness of strength-based counseling on self-worth of divorced women - Parsakia, Kamdin; Darbani, Seyed Ali (Applied Family Therapy Journal (AFTJ), 2022)
Aim: This study aimed to investigate the effectiveness of strength-based counseling in increasing the sense of self-worth of divorced women. Method: This research was quasi-experimental with a pre-test-post-test design with a control group. This research's statistical population was divorced women referred to Mehravar Counseling Center in Tehran in 2021. Among those who had obtained a lower score on the self-esteem scale of Crocker et al. (2003), a sample of 20 people was randomly selected and assigned to two experimental groups (10 people) and control groups (10 couples). The experimental group members received ten 90-minute sessions of Smith's (2006) strength-based intervention as a group, and the members of the control group were placed on the waiting list. Both groups responded to the self-esteem scale before and after the experiment. Analysis of covariance was used to analyze the data. Results: The results showed that strength-based counseling significantly increased self-esteem scores (F=63.23, P=0.001) and its subscales: family support (F=46.31, P=0.001); Divine Love (F=32.10, P=0.001); Scientific competence (F=29.58, P=0.001); piety and piety (F=6.16, P=0.019). This increase was stable in the follow-up phase. Conclusion: Based on the findings, it can be concluded that counseling based on strength increases the self-worth of divorced women.